Digital Islamic Propagation Communication Strategies in Countering Religious Disinformation in the Post-Truth Era: A Literature Study - Mastori, Mastori; Bahtiar, Ace Thoyib; Gunawan, Chandra; Dale, Ridho (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2025)
One of the negative impacts of the development of digital technology is the weakening of authoritative facts and the increasing dominance of opinion in the public sphere. This situation strengthens the spread of religious disinformation in digital media, which has the potential to shift the authenticity of Islamic thought. Departing from this fact, this study seeks to analyze how da'wah communication strategies can function as a mechanism to counter religious disinformation in the post-truth context. This study uses a qualitative method with a literature study approach to articles or books published between 2016 and 2024. The data was obtained through a systematic search process in the Google Scholar database, books, and various research results. The literature selection was based on the following criteria: relevance to the theme of digital da'wah communication, media literacy, and post-truth studies; and publications that provide empirical findings or theoretical frameworks related to countering disinformation. The analysis results show three main findings: first, implementing effective digital da'wah communication practices in the post-truth era consistently utilizes the principle of ttabayyun as an information verification mechanism; second, increasing digital literacy among da'i and audiences has been proven to be a factor that directly reduces vulnerability to misinformation and disinformation; Third, creative, data-driven da'wah content that adheres to digital communication ethics has a higher level of reach and public trust. This third finding demonstrates that digital da'wah communication plays a crucial role as a social instrument for maintaining the integrity of religious information amidst the dominance of opinion in the post-truth era.